A Review of Irish Energy Policy - FITZGERALD, JOHN (ESRI, 2011)
This paper reviews the considerable body of economic research on energy in Ireland and elsewhere. It draws out the implications of this research for Irish energy policy, and also some of the implications for EU energy and environmental policy. The paper identifies some important gaps in our knowledge, gaps which need to be filled to inform policymakers of the full implications of policy choices which they are currently facing.
PUBLISHED
Dublin
Keywords: Economics; Irish Energy Policy